MODEL PENDAMPINGAN ORANGTUA DALAM PENGGUNAAN MEDIA SMARTPHONE UNTUK MENINGKATKAN MUTU PEMBELAJARAN (Penelitian Pada Orangtua di PGTK Pasim Ar-rayyan, KB/PAUD An-Najwa dan RA Lijamul Athfal Sukabumi) - Devi Cahya Permata; Achmad Mudrikah; Hanafiah Hanafiah (JURNAL PAUD AGAPEDIA, 2022)
Learning that was originally with the face-to-face method has now been changed to online learning. This raises problems, especially the implementation of learning for early childhood. Learning is carried out using communication technology media, one of which is a smartphone. In its application, parental assistance is needed because early childhood cannot learn on their own without assistance from parents. The concept of online learning that can be implemented in a learning process is the basic concept initiated by George R. Terry known as POAC (Planning, Organizing, Actuating and Controling). The specific objectives of this study were to obtain an overview of: 1) Planning, 2) Organizing, 3) Implementation and 4) Assessment of parental assistance models in the use of smartphone media to improve the quality of learning. The research method uses a qualitative approach with a descriptive method. The research data were collected by using observation, interview, documentation, and triangulation techniques. The research locations were PGTK Pasim Ar-Rayyan, KB/PAUD An-Najwa and RA Lijamul Athfal Sukabumi. The theory that underlies this research is the model of parental assistance and the quality of learning. The results of this study include: 1) The learning planning carried out by the institution refers to the emergency curriculum and is designed flexibly or adapted to conditions; 2) The organization of learning materials that have been designed is made as creative as possible and involves all parties; 3) The implementation of learning is carried out on the learning method while playing and the Institute cooperates with parents in the implementation of learning; 4) Assessment of the learning process according to the required data, students collect assignments, attendance so that principals and tutors can evaluate the learning process of students. Conclusions of research results 1) Research subjects carry out lesson plans that refer to the emergency curriculum and design flexible learning plans; 2) Organizing early childhood learning, namely organizing time, human resources and teaching materials; 3) The implementation of learning is carried out through indirect learning using supporting media, namely smartphones; 4) Assessment by collecting data and information on activities carried out by children on a daily basis. Pembelajaran yang semula dengan metode tatap muka kini diubah menjadi pembelajaran daring/online. Hal tersebut menimbulkan problematika khususnya pelaksanaan pembelajaran bagi anak usia dini. Pembelajaran dilaksanakan dengan menggunakan media teknologi komunikasi salah satunya smartphone. Dalam penerapannya, diperlukan pendampingan orangtua karena anak usia dini tidak dapat belajar sendiri tanpa adanya pendampingan dari orang tua. Konsep belajar secara daring/online yang bisa diimplementasikan dalam sebuah proses pembelajaran yaitu konsep dasar yang digagas oleh George R. Terry yang dikenal dengan POAC (Planning, Organizing, Actuating and Controling). Tujuan khusus penelitian ini adalah untuk memperoleh gambaran tentang: 1) Perencanaan, 2) Pengorganisasian, 3) Pelaksanaan dan 4) Penilaian model pendampingan orangtua dalam penggunaan media smartphone untuk meningkatkan mutu pembelajaran. Metode penilitian menggunakana pendekatan kualitatif dengan metode deskriptif. Data penelitian dikumpulkan dengan teknik observasi, wawancara, dokumentasi, dan triangulasi. Lokasi penelitian di PGTK Pasim Ar-rayyan, KB/PAUD An-Najwa dan RA Lijamul Athfal Sukabumi. Teori yang melandasi penelitian ini adalah model pendampingan orangtua mutu pembelajaran. Hasil penelitian ini diantaranya : 1) Perencanaan pembelajaran yang dilakukan lembaga mengacu pada kurikulum darurat dan dirancang secara fleksibel atau disesuaikan dengan kondisi; 2) Pengorganisasian materi pembelajaran yang telah dirancang dibuat sekreatif mungkin dan melibatkan semua pihak; 3) Pelaksanaan pembelajaran dilaksanakan pada metode belajar sambal bermain dan Lembaga bekerjasama dengan orangtua dalam pelaksanaan pembelajaran; 4) Penilaian proses pembelajaran sesuai data yang diperlukan, peserta didik mengumpulkan tugas, kehadiran sehingga kepala sekolah dan tutor dapat mengevaluasi proses pembelajaran peserta didik. Simpulan hasil penelitian 1) Subyek penelitian melakukan perencanaan pembelajaran yang mengacu pada kurikulum darurat dan merancang perencanaan pembelajaran secara fleksibel; 2) Pengorganisasian pembelajaran anak usia dini yaitu melakukan pengorganisasian waktu, SDM dan bahan ajar; 3) Pelaksanaan pembelajaran dilakukan melalui pembelajaran tidak langsung menggunakan media penunjang yaitu smartphone; 4) Penilaian dengan mengumpulkan data dan informasi kegiatan yang dilakukan anak sehari-hari.